The future of energy : challenges, perspectives, and solutions - Valone, Thomas (Energy Policies, Politics and Prices Ser., 2020)
"The anthology entitled, "The Future of Energy: Challenges, Perspectives, and Solutions" includes a wide range of topics related to the probable and also possible future developments of energy technologies. The collection of papers offers a series of unprecedented perspectives on energy science, unavailable elsewhere. The authors have considered developments in renewable energy, novel energy discoveries, environmental climate futures, possible technological advances, temporal distortion, and gravitational electromagnetism. Specific energy inventors reporting breakthrough results have also been showcased in individual chapters, including Searl, Manelas, Kozyrev, and Storms. The future of energy is presented with possible scenarios such as with microgrids, solar systems, fusion-fission reactors, smart cities, energy storage, electric vehicles, low energy nuclear reactors, electromagnetic devices, proton and electron conversion, theoretical antigravity, and time manipulation. Several interesting models have been considered to provoke and stretch the reader's imagination and awareness of the study of the future. This collection of works provides a broad range of conceptual understanding of energy conversion that is both conventional and unconventional. Each chapter includes a significant use of graphs and charts, as well as explanatory equations where necessary, with plenty of vital references and links to substantiate any new scientific concepts and assist further research. More than one new phenomena of electrical power production have been discovered and the results documented in detail within the pages of this anthology. While the time schedule and specific cause of global warming is detailed, the plan for advanced energy applications is also explored. The collection of works provides a unique perspective on the evolving landscape of future energy which is provocative and enlightening. The reader will find it enriches and enlivens the discussion of what is to come"--